PERAN SIKAP KONSUMEN DALAM MEMEDIASI PENGARUH RELIGIUSITAS DAN REPUTASI MEREK TERHADAP MINAT BELI ULANG - Ken Sudarti; Salim Bakhrul Ulum (Jurnal Ekonomi dan Bisnis, 2019)
This research is brainstormed by the franchise business which develops rapidly. There are somany franchise trade marks which are developed in Indonesia especially in Semarang suchas Kentucky Fried Chicken (KFC). McDonald, Pizza Hut, Hoka-Hoka Bento, etc. As a fast foodrestaurant, KFC has so many competitors which always compete to satisfy the costumers. Inorder to attract the customers, KFC has to improve the quality of taste, services and productinnovations. It is done in order to keep the reputations of its trade mark and improve therepurchase intention. Based on the phenomenon above, the research focuses to analyze howto improve the repurchase intention of KFC product in Semarang based on religiosity, reputationof trade mark and the customers attitude. The object of the research are the customers of KFCin Semarang city which involves 100 responders. The sampling technique used in this researchis purposive sampling. It is a sampling technique based on current criteria. The data collectinguses questioners which opened questions and closed questions. The data analysis uses doubleregresi linier and sobel test with SPSS. The result of the analysis shows that the religiosity andreputation of trade mark has a positive and significant impact on repurchase intention.Keywords : Religiosity, Reputation Of Trade Mark, Customer Attitude and Repurchase Intention